Penerapan Model Pembelajaran Giving Question and Getting Answer Berbantuan Media Wordwall Random Cards untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran Ekonomi (Studi Quasi Eksperimen Pada Peserta Didik Kelas XI IPS SMA Negeri 5 Tasikmalaya Tahun Ajaran 2023/2024) - Ermawati, Sri; Gumilar, Rendra (LPPM Institut Pendidikan Nusantara Global, 2024)
T The research was motivated by the problems that occurred at SMAN 5 Tasikmalaya, namely the low learning outcomes of students. The aim of the research is to determine the effect of implementing the learning model giving question and getting answer media assisted wordwall random cards to improve student learning outcomes in economics subjects, international trade material. The method used is method quasi experiment with research design non-equivalent control group design, as well as data collection techniques through multiple choice tests. The research population of all class XI IPS at SMAN 5 Tasikmalaya for the 2023/2024 academic year was 179 students. The samples used were class XI IPS 2, totaling 36 people as the experimental class and class purposive sampling. Based on the research results, it is clear that there is an influence of learning models giving question and getting answer media assisted wordwall random cards in improving student learning outcomes in economics subjects, international trade material, where Ha is accepted if the value Sig. (2-tailed) ≤ 5% or 0.05 and based on the research results the value is obtained Sig. (2-tailed) equal to 0.000 < 0.05. The average score of the experimental class is higher than the control class, thus it can be concluded in this study that the learning model giving question and getting answer media assisted wordwall random cards can improve student learning outcomes.